(untitled) (Research, Society and Development, 2021)
The anxiety disorders belong to a group of mental disorders in which the patients present excessive fear and worry. Studies with ferulic acid have shown positive results on treating depressive symptoms. As many antidepressive drugs are effective in treating anxiety, the objective of the present study was to evaluate ferulic acid’s anxiolytic activity and possible mechanism of action in the light-dark test in zebrafish. To evaluate anxiolytic activity, the light-dark preference test was performed after exposure of the animals to ferulic acid or positive control (clonazepam or fluoxetine). Ferulic acid increased the time spent in the clear compartment at concentrations of 250 and 500 mg/L, not differing from the groups exposed to clonazepam or fluoxetine. To evaluate the possible mechanism of action, pre-exposure to flumazenil was carried out, followed by exposure to ferulic acid or positive control, with subsequent testing. Pre-exposure to flumazenil caused a significant reduction in the time spent in the clear compartment of ferulic acid and clonazepam groups but did not alter the effect of exposure to fluoxetine. These results suggest that ferulic acid promotes an anxiolytic effect, possibly through an action at the benzodiazepine binding site at the GABAA receptor.